Gestão de custos e formação de preços em uma fábrica de pré-moldados de Mossoró - Silva, Jordana Marjorie Holanda (Universidade Federal Rural do Semi-Árido, 2021)
The search for competitive prices grows more and more in the market, and with that the search for a balanced pricing with the competition also grows. In the civil construction sector it could not be different, with a market that has high competition, precast manufacturing companies seek to stand out in some way and their price is always the main point to be analyzed and so that there are competitive prices it is necessary that they are offered correctly. Thus, costing and pricing methods are used to assist in this search. Thus, this study aims to present a methodology to help in cost management and in the price formation process of a precast factory in Mossoró-RN, providing information to help managers in decision making. In order to achieve this goal, the study seeks to define a pricing method through the use of direct manufacturing costs together with the Mark-up, calculated at 77%, and the analysis of contribution margins and break-even point. Thus, it is concluded that with the work it was possible to observe the importance of having a good cost management and also calculate the break-even point so that the minimum revenue is known. Thus, the proposed method is effective when applied correctly and is also easy to implement and understand
Keywords: Gestão de custos; Precificação; Pré-moldado; Ponto de equilíbrio; Margem de contribuição; Cost management; Pricing; Precast; Balance point; Contribution margin; ENGENHARIAS::ENGENHARIA DE PRODUCAO